Autonomía institucional de los centros educativos presupuestos, organizacion y estrategias - Villa, Aurelio; Gairín Sallán, Joaquín. (Bilbao : Universidad de Deusto, 1994)
Title: "Institutional Autonomy of Educational Centers: Premises, Organization, Strategies" (Translation). "The proceedings of a conference dedicated to exploring institutional autonomy as it concerns Spanish educational centers. Covened at a time when decentralization was taking place in educational centers across Europe, and written from the standpoint that institutional autonomy is the central factor in determining how a center can carry out its mission, this book is divided into four parts: overview of institutional autonomy in educational centers, autonomy and its relation to the educational experience, the experience of self-management, and strategies for the development of institutional autonomy."--From introduction (translated) Key terms. Places: Spain--Periods: 20th century--Forms: Congresses--Forms: Education.
Includes bibliographical references.
Keywords: School management and organization; Electronic books